2006
DOI: 10.1111/j.1744-313x.2006.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 gene polymorphisms and natural soluble CTLA‐4 protein in psoriasis vulgaris

Abstract: CTLA-4 molecule is an important inhibitor of T-lymphocyte activation. Several single nucleotide polymorphisms (SNPs) in the CTLA-4 gene were found, and their associations with many human diseases were described. So far, however, such studies have not been performed in psoriasis vulgaris in Caucasoids. Therefore, we examined the distribution of three CTLA-4 SNPs: -1147C/T, -318C/T and +49 A/G in 116 patients with psoriasis vulgaris and 123 healthy blood donors using the polymerase chain reaction-restriction fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
0
18
2
Order By: Relevance
“…Studies of correlations of sCTLA-4 levels with disease activity in other autoimmune diseases gave inconsistent results. sCTLA-4 was found to correlate with autoantibodies against nicotinic acetylcholine receptors in myasthenia gravis (21) and area of skin lesions and severity of index values in psoriasis vulgaris (24), but not with disease activity in systemic lupus erythematosus (15). Our observations refute a potential utility of sCTLA-4 as a biochemical marker of ocular change activity, but may testify in favor of a predominantly genetic over an environmental regulation of sCTLA-4 synthesis.…”
Section: Discussioncontrasting
confidence: 43%
“…Studies of correlations of sCTLA-4 levels with disease activity in other autoimmune diseases gave inconsistent results. sCTLA-4 was found to correlate with autoantibodies against nicotinic acetylcholine receptors in myasthenia gravis (21) and area of skin lesions and severity of index values in psoriasis vulgaris (24), but not with disease activity in systemic lupus erythematosus (15). Our observations refute a potential utility of sCTLA-4 as a biochemical marker of ocular change activity, but may testify in favor of a predominantly genetic over an environmental regulation of sCTLA-4 synthesis.…”
Section: Discussioncontrasting
confidence: 43%
“…On the other hand, sCTLA-4 may similarly inhibit the interaction of the cell membrane-anchored CTLA-4 molecule with CD80 and CD86, thus blocking the inhibition of T-cell activation [20]. In light of the findings mentioned above, it has been hypothesized that elevated sCTLA-4 concentration in PS results in its successful competition with activated T-cell membrane-anchored CTLA-4 for interaction with CD80/CD86 ligands, weakening the control over T-cell response and resulting in the aggravation of disease symptoms [26]. Although in our study CTLA-4 exon 1 polymorphism was not associated with susceptibility to PS, other variants such as T/C-1772, associated with levels of sCTLA-4 in sera [27], could play an important role in this autoimmune disease.…”
Section: Discussionmentioning
confidence: 95%
“…The increased serum levels of sCTLA-4, produced by resting T cells, could reduce CTLA-4 inhibitory function by competing with mCTLA-4 for binding to CD80/CD86 ligands on APCs [36]. Elevated sCTLA-4 concentration resulted in its successful competition with activated T-cell membrane-anchored CTLA-4 for interaction with CD80/CD86 ligands in psoriasis vulgaris, weakening the control over T-cell response and resulting in the aggravation of disease symptoms [37]. In fact, some studies found that the CTLA-4 Ϫ318C/T polymorphism had been associated with the risk of several autoimmune diseases and various malignancies [38 -41].…”
Section: Discussionmentioning
confidence: 96%